First reported case of subcutaneous hyalohyphomycosis caused by Paecilomyces variotii. (17th May 2013) - Vasudevan, Biju; Hazra, Nandita; Verma, Rajesh; Srinivas, Vadlamannati; Vijendran, Pragasam; Badad, Ambresh
Abstract Background Hyalohyphomycosis is a rare opportunistic fungal infection caused by saprophytes of genera such as Fusarium, Paecilomyces, Scedosporium, Penicillium, Scopulariopsis Acremonium, and similar fungi. The literature includes only one previous report of Paecilomyces variotii human infection and very few reports of subcutaneous mycosis caused by any of the hyalohyphomycosis group of fungi. Methods We report an instance of fungal infection in a 50‐year‐old woman, known to have diabetes, who presented with multiple raised lesions on the upper back of two years' duration. Dermatological examination revealed a 20 × 22‐cm, swollen, indurated area on the upper back with multiple violaceous, exophytic nodules on the surface. Results Microscopy from pus and tissue smear revealed septate branching fungi. Periodic acid Schiff (PAS) stain was positive for fungal elements. Culture on three occasions yielded P. variotii. Slide culture mounts showed septate hyaline hyphae of P. variotii with elongated phialides demonstrating bulbous bases and tapering apices attached to the conidiophores. The patient was treated with itraconazole, to which she responded well. Conclusions This is the first reported case of subcutaneous hyalohyphomycosis caused by P. variotii. It appears that this relatively rare fungal pathogen may be starting to assert itself as an important cause of infection in humans.